ICCA intelligence : international association meetings : bidding and decision-making (ICCA AmsterdamNL, 2009)
Presents a comprehensive set of guidelines and check-lists which are created to help international association executives evaluate and improve the methodology they use to decide on future destinations for their international meetings.
Keywords: CONFERENCES